COVID-19 knowledge, attitude, and practices among the Rohingya refugees in Cox's Bazar, Bangladesh - Md. Fahad Jubayer; Md. Tariqul Islam Limon; Md. Masud Rana; Md. Shahidullah Kayshar; Md. Shoaib Arifin; AHM Musleh Uddin; Md. Anisur Rahman Mazumder (Elsevier, 2022)
Objectives: The Rohingya refugee population in Bangladesh has become more vulnerable to COVID-19 because of their living and environmental conditions. The aim of the study was to represent an assessment of the Rohingya people's COVID-19-related knowledge, attitude, and practices (KAP) at eight refugee camps in Cox's Bazar. Study design: Cross-sectional study. Methods: This study was completed with a total of 400 responses between July and September of 2020. A questionnaire was created to assess demographic characteristics (5 items), knowledge (10 items), attitude (5 items), practices (5 items), and information sources (1 item). Aside from the KAP scores, the scores are also presented based on demographic variables. Results: The KAP of the respondents were not satisfactory, with scores of 5.8 ± 1.8, 2.2 ± 1.0, and 0.9 ± 0.7, respectively. We found significant differences only in the knowledge scores based on education and gender. Conclusion: In conclusion, this study emphasizes the importance of COVID-19 training that focuses on behavioral changes for the Rohingya people in Bangladesh.